Remarriage in the Orthodox Church Challenges Catholic Church - Vasiľ, Cyril (Studia canonica, 2013)
The growing presence of Orthodox immigrants in Catholic regions requires a study of the discipline which governs marriages between Catholics and Orthodox. These unions are regulated by divine law and also by canon law—Catholic and Orthodox—and can be celebrated in the Catholic Church or the Orthodox Church. Divine law impediments render these marriages impossible. Since the alleged or so-called 'Orthodox divorce' is not recognized by Catholics, it is necessary each time to obtain a declaration of nullity from the Catholic diocesan tribunal.